Electrochemical reforming of glycerol into hydrogen in a batch-stirred electrochemical tank reactor equipped with stainless steel electrodes: Parametric optimization, total operating cost, and life cycle assessment. Issue 4 (August 2022) - Peralta-Reyes, Ever; Vizarretea-Vásquez, Diego; Natividad, Reyna; Aizpuru, Aitor; Robles-Gómez, Edson; Alanis, Claudia; Regalado-Méndez, Alejandro
Abstract: The electrochemical reforming of glycerol was carried out in a batch-stirred electrochemical tank reactor equipped with stainless steel electrodes. A response surface methodology constituted by a Face-Centered Central Composite Design was performed to establish the optimal operational conditions to produce hydrogen. Studied parameters were glycerol concentration ( C G ), current intensity ( I ) and temperature ( T ), while chosen responses were hydrogen and oxygen concentrations ( C H 2 and C O 2 ). A maximum C H 2 (79.18 mg/L) and minimum C O 2 (46.24 mg/L) with a global desirability of 67%, were achieved at multi-optimal conditions, including C G, = 3.46 mol/L, I = 5.21 A, and T  = 70 °C. All studied parameters were significant for both chosen responses ( η C H 2 and η C O 2 ) since all values of the sensitivity index were higher than 0.5. The analysis of interaction between parameters suggests than C G and T simultaneous increase will bring a decrease in C H2 . The experimental data were fitted to a quadratic polynomial surrogate model, with correlation coefficients of 0.9801 and 0.9967 for η C H 2 and η C O 2, respectively. The reduced root-mean-square error was 0.065 and 0.054 for η C H 2 and η C O 2, respectively. This suggests a successful optimization of the BSETR operational parameters. The hydrogen production process assessed in this work, is a promising green energy technology that uses waste glycerol as a carbon-based fuel and a low-cost anode material (7.5 USD¢/kg H2 ) as stainless steel. The carbon footprint of the hydrogen production by the optimized process is 0.192 kg CO2 eq and this can be reduced 92.1% when using a solar photovoltaic system to energize the electrodes. Graphical Abstract: ga1 Highlights: Glycerol electrochemical reforming was successfully conducted in a BSRTR achieving a 13.29% of glycerol conversion at 80 min. Optimal operating variables of glycerol electrochemical reforming are C G = 3.46 mol/L, I = 5.21 A, T = 70 °C, and t  = 80 min. Green hydrogen production cost by glycerol electrochemical reforming process is 2.74 USD$/kg H2 . Carbon footprint of the optimized hydrogen production by glycerol electrochemical reforming (0.192 kg CO2, eq ) was determined by LCA. Carbon footprint of the studied process can be reduced 92.1% if solar PV energy is used.